The ballasting effect of Saharan dust deposition on aggregate dynamics and carbon export: Aggregation, settling, and scavenging potential of marine snow. (19th February 2018) - van der Jagt, Helga; Friese, Carmen; Stuut, Jan‐Berend W.; Fischer, Gerhard; Iversen, Morten H.
Abstract: Lithogenic material such as Saharan dust can be incorporated into organic aggregates and act as ballast, potentially enhancing the marine carbon export via increased sinking velocities of aggregates. We studied the ballasting effects of Saharan dust on the aggregate dynamics in the upwelling region off Cape Blanc (Mauritania). Aggregate formation from a natural plankton community exposed to Saharan dust deposition resulted in higher abundance of aggregates with higher sinking velocities compared to aggregate formation with low dust. This higher aggregate abundance and sinking velocities potentially increased the carbon export 10‐fold when the aggregates were ballasted by Saharan dust. After aggregate formation in the surface waters, subsequent sinking through suspended Saharan dust minerals had no influence on aggregate sizes, abundance, and sinking velocities. We found that aggregates formed in the surface ocean off Mauritania were already heavily ballasted with lithogenic material and could therefore not scavenge any additional minerals during their descent. This suggests that carbon export to the deep ocean in regions with high dust deposition is strongly controlled by dust input to the surface ocean while suspended dust particles in deeper water layers do not significantly interact with sinking aggregates.